1996
DOI: 10.1111/j.1651-2227.1996.tb14196.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin A in relation to socio‐economic, demographic and dietary characteristics in Bangladeshi children

Abstract: The purpose of this study was to examine socio-economic conditions, demographic factors, use of vitamin A capsules and dietary practices in relation to the risk of low serum vitamin A. One hundred and twenty four night blind cases were identified by parents in a cross-sectional survey in Bangladesh in 1992. Age-, sex- and neighbourhood-matched controls were selected. Venous blood was collected from 87 cases and 97 controls for the determination of serum vitamin A. Information about socio-economic conditions, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
4
2
Order By: Relevance
“…Although not signi®cant in the multivariate analysis model, this should not be overlooked, as evidence from Ghana indicated that the level of per capita consumption is substantially lower in households headed by divorced and widowed women than in those headed by married women 19 . Although we could not show an association between dietary practices and vitamin A status, this aspect should not be ignored since a strong association between serum vitamin A levels and the frequent consumption of foods rich in b-carotene and vitamin A has been reported 20 . The appropriate lack of association between dietary practices and vitamin A levels found in our study could be because of small sample size, or monotonous dietary practices.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although not signi®cant in the multivariate analysis model, this should not be overlooked, as evidence from Ghana indicated that the level of per capita consumption is substantially lower in households headed by divorced and widowed women than in those headed by married women 19 . Although we could not show an association between dietary practices and vitamin A status, this aspect should not be ignored since a strong association between serum vitamin A levels and the frequent consumption of foods rich in b-carotene and vitamin A has been reported 20 . The appropriate lack of association between dietary practices and vitamin A levels found in our study could be because of small sample size, or monotonous dietary practices.…”
Section: Discussioncontrasting
confidence: 60%
“…Although we could not show an association between dietary practices and vitamin A status, this aspect should not be ignored since a strong association between serum vitamin A levels and the frequent consumption of foods rich in b-carotene and vitamin A has been reported 20 . The appropriate lack of association between dietary practices and vitamin A levels found in our study could be because of small sample size, or monotonous dietary practices.…”
Section: Discussioncontrasting
confidence: 60%
“…The impact of this traditional food on serum retinol levels is not yet clear. Although de Pee et al (1995) showed that dark-green leafy vegetables had no effect on vitamin A status, because of their low bio-availability, among 2-15-year-old children in Bangladesh serum vitamin A levels were strongly associated with food intake, the most significant association being with consumption of dark-green leafy vegetables (Hussain & Kvåle, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese men, a positive association was found between changes in the intake frequency of green and yellow vegetables and changes in serum b-carotene levels 15 . Although de Pee et al showed that dark-green leafy vegetables had no effect on vitamin A status because of their low bioavailability 16 , among 2±15-year-old children in Bangladesh serum vitamin A levels were strongly associated with food intake, the most significant association being with consumption of dark-green leafy vegetables 17 . In children aged 2±6 years consumption of green leafy vegetables with added fat resulted in improved vitamin A status 18,19 .…”
mentioning
confidence: 97%